THE DEVELOPMENT OF HIGHER-ORDER THINKING SKILLS ON JUNIOR HIGH SCHOOL STUDENTS THROUGH GUIDED INQUIRY-BASED LEARNING APPROACH - Purwasi, Lucy Asri (Jurnal Pendidikan Matematika dan IPA, 2020)
This study was aimed to determine the development levels of higher-order thinking skills on students through the guided inquiry-based learning approach. The research method used was experimental, with true empirical design research. The sample selection was performed by random sampling technique. Data was collected through five tests of essay forms in accordance with various indicators of higher-order thinking abilities, including analysing (C4), evaluating (C5) and creating (C6). The results of this study indicated that the percentage of higher-order thinking ability in the experimental class was 86%, while in the control class was lower, at 79.3%. Based on the results of the study, it was concluded that students with higher-order thinking skills taught through this guided inquiry-based learning were superior compared to those taught by conventional learning.AbstractThis study was aimed to determine the development levels of higher-order thinking skills on students through the guided inquiry-based learning approach. The research method used was experimental, with true empirical design research. The sample selection was performed by random sampling technique. Data was collected through five tests of essay forms in accordance with various indicators of higher-order thinking abilities, including analysing (C4), evaluating (C5) and creating (C6). The results of this study indicated that the percentage of higher-order thinking ability in the experimental class was 86%, while in the control class was lower, at 79.3%. Based on the results of the study, it was concluded that students with higher-order thinking skills taught through this guided inquiry-based learning were superior compared to those taught by conventional learning.Keywords: Guided Inquiry-based Learning, Conventional Learning, Higher-Order Thinking Skills